2019
DOI: 10.1103/physrevb.99.125109
|View full text |Cite
|
Sign up to set email alerts
|

Charge-carrier behavior in Ba-, Sr- and Yb-filled CoSb3 : NMR and transport studies

Abstract: We report 59 Co NMR and transport measurements on n-type filled skutterudites BaxYbyCo4Sb12 and AxCo4Sb12 (A= Ba, Sr), promising thermoelectric materials. The results demonstrate consistently that a shallow defect level near the conduction band minimum dominates the electronic behavior, in contrast to the behavior of unfilled CoSb3. To analyze the results, we modeled the defect as having a single peak in the density of states, occupied at low temperatures due to donated charges from filler atoms. We fitted the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Thus, the analysis of the electrical behavior inside a material involves a detailed description of the behavior of electrons and holes. Electron thermal conductivity describes the thermal conductivity, which can be solved by Wiedemann-Franz law [9].…”
Section: The Thermoelectric Figure Of Merit Zt Of Thermoelectric Mate...mentioning
confidence: 99%
“…Thus, the analysis of the electrical behavior inside a material involves a detailed description of the behavior of electrons and holes. Electron thermal conductivity describes the thermal conductivity, which can be solved by Wiedemann-Franz law [9].…”
Section: The Thermoelectric Figure Of Merit Zt Of Thermoelectric Mate...mentioning
confidence: 99%
“…Recently, several studies focused on multiple-filled skutterudites [13,14]. Xun Shi et al, [14] reported that there are a few doped samples which show an improved figure of merit of 1.7 at around 850 K. This ZT is one of the highest 25 value reported in skutterudites type of TE materials.…”
Section: Introductionmentioning
confidence: 97%
“…13 crystallize in a cubical form with space group of 217(I43m)wherein half of the Cu atoms occupy four-coordinate distorted tetrahedral sites 100 (Cu1) and other half occupy three-coordinate triangular sites (Cu2) with total 58 atoms per unit cell. Therefore, half of 24 Cu sites are occupied by twelve Cu-I sites and other half by twelve Cu-II sites.Figure 1shows the calculated density of states.…”
mentioning
confidence: 99%
“…ZrCoSb-based materials have also been widely studied and shown promising zT and low thermal conductivity [4]. To better understand the mechanism and further improve thermoelectric performance, the NMR technique can be used as a local probe to reveal information about electronic properties, phonon behaviors and native defects [5,6,7]. In this work, we have applied NMR in studying members of this series of transition-metal-based half-Heusler materials, focusing in particular on trends in the electronic properties in this thermoelectric materials family.…”
Section: Introductionmentioning
confidence: 99%